Analyzing blameworthiness in the bubble and chamber - Uri, Angel Yvette G (Animo Repository, 2024)
Tracing back to how false beliefs are acquired and exacerbated by victims who are inside the epistemic bubble and echo chamber environments, it seems like these victims have no control over the acquisition and corruption of their belief structures. This is especially true for echo chamber victims because of the combination of the constant polarization and credibility manipulation that they experience. This results in the cultivation of implicit biases over beliefs inside the chamber. Now, can we say that these victims are epistemically blameworthy for having false beliefs? Furthermore, are these victims all the same in terms of their traits and blamelessness or blameworthiness? In this paper, I examine and emphasize the differences between victims of epistemic bubbles and echo chambers through the lens of epistemic blameworthiness. I argue that epistemic bubble and echo chamber victims have different traits, statuses, and epistemic responsibilities. By identifying their epistemic blameworthiness, the epistemic profiles enumerate six types of epistemic bubbles and echo chambers. This proves that not all victims of epistemic bubbles and echo chambers are similar. They have different profiles which will be used to prove their epistemic blamelessness and blameworthiness, thereby, creating a preliminary basis for the criteria for the degrees of epistemic blameworthiness for epistemic bubble and echo chamber victims.